Relationship of Nutritional Status Towards Correct Motor Development in Toddlers at Keluk Pakis Full Star Posyandu, Pekanbaru City, 2021 - Nur Israyati (Institute Of Computer Science (IOCS), 2021)
Nutrition is very influential on the gross motor development of children. Good nutritional status can help the process of growth and development of children to reach optimal maturity. The impact of more nutritional status will cause excessive weight problems. As a result, the child has an excessive burden, of course it will interfere with motor skills because in carrying out motion there is no balance between the body and the center of gravity and also requires a lot of energy. The purpose of this study was to determine the relationship between nutritional status and gross motor development in toddlers at the Keluk Pakis Posyandu, Pekanbaru City in 2021. This study used a quantitative research type, with an analytical design. And using a cross sectional approach. The number of samples studied were 15 children. The measuring instrument used is a checklist table adapted from several related literatures. The results showed that there was a significant relationship between nutritional status and gross motoric development of toddlers, where X2 Count > X2 Table ie 4.17 > 2.706 so Ha was accepted and Ho was rejected. It is hoped that the Puskesmas, especially posyandu cadres, will continue to carry out preventive efforts such as providing information in the form of counseling to the community to prevent children from experiencing malnutrition (stunting), increasing awareness of parents of toddlers about nutritional status and gross motor development by paying more attention to development and nutritional status so that the number of children under five is expected to increase. Those who experience poor nutritional status or whose gross motor development fails can be reduced, providing stimulation to children for the surrounding environment, especially parents so that children can be stimulated by ideas in the hope of improving the gross motor development of children who are late.